2018
DOI: 10.1016/j.whi.2017.11.005
|View full text |Cite
|
Sign up to set email alerts
|

Impacts of the Affordable Care Act's Medicaid Expansion on Women of Reproductive Age: Differences by Parental Status and State Policies

Abstract: The ACA Medicaid expansion increased insurance coverage for low-income women of reproductive age, with the greatest effects for women without dependent children and women residing in states with relatively lower pre-ACA Medicaid eligibility levels or with no family planning waiver before the ACA.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
68
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 68 publications
(71 citation statements)
references
References 29 publications
(45 reference statements)
2
68
1
Order By: Relevance
“…These would be important directions for future research, given documented differences in perinatal insurance coverage by race, ethnicity, and parental status. 14,33 Fifth, we were not able to adjust for multiple comparisons in our analyses.…”
Section: Study Data and Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…These would be important directions for future research, given documented differences in perinatal insurance coverage by race, ethnicity, and parental status. 14,33 Fifth, we were not able to adjust for multiple comparisons in our analyses.…”
Section: Study Data and Methodsmentioning
confidence: 99%
“…This change led to an immediate and large increase in insurance coverage among low-income women of reproductive age in expansion states when compared with nonexpansion states. 14 In general, women without children experienced the largest changes in insurance coverage after the ACA Medicaid expansions, although women with children in states with low parental eligibility thresholds also experienced large increases in insurance coverage. The Medicaid expansions and other ACA coverage expansions improved access to care for reproductive-age women, including increased access to physicians and fewer cost barriers to receiving care.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…A random digit dialing method is used to select a representative sample of respondents from the noninstitutionalized adult population. BRFSS has been extensively used to research health impacts of the ACA [5, 1821]. It is particularly appropriate because its large number of observations, more than 300,000 per year, allows us to decipher the effects of the ACA.…”
Section: Methodsmentioning
confidence: 99%
“…In contrast, women in expansion states can remain covered after delivery if still income eligible as an expansion adult and thus benefit from continuous coverage and better access to care, including earlier entry into prenatal care, if they were to become pregnant again. A study published in 2017 and using Behavioral Risk Factor Surveillance System data found that Medicaid expansions significantly decreased the uninsured rate among poor (<100% FPL) women of reproductive age (19-44 years) between 2012 and 2013 and 2014 and 2015 by 13.2% (48% were uninsured in 2012-2013 and 39.6% were uninsured in 2014-2015) (Johnston, Strahan, Joski, Dunlop, & Adams, 2018). In 2014, the most recent year available for national enrollment estimates, 25 million of the 69.3 million individuals enrolled in Medicaid were women older than 19 years of age (representing 36% of total Medicaid enrollment); of these 25 million women, the vast majority, 67%, were of reproductive age (19-49 years old) (Kaiser Family Foundation, 2019).…”
mentioning
confidence: 99%